Slovenia: From the Protection of Acquired Rights, Legitimate Expectations and the Principle of Solidarity to Financial Sustainability Constrains— What Does the Future Hold? - Mišič, Luka; Strban, Grega (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
This chapter, grounded in most relevant Slovenian literature on social security law, provides a general overview of the Slovenian social security system. However, the authors approach the overview from the perspective of long-term sustainability, adding specific topics, such as the potential future interplay between public and private income responsibility, upcoming healthcare and pension reform, and the introduction of new branches of social insurance, to the general overview. Examining the Slovenian Constitution, they address distinct social security (social insurance) schemes, such as the mandatory health insurance, pension and disability, or the developing long-term care insurance scheme, alongside the social assistance scheme, which is in place as a subsidiary safety net aimed at preventing poverty and social exclusion. The authors briefly address other notions in social security, such as social damages and cover the basic elements of social procedural law. Further, they address substantial and formal or organisational aspects of social security or social security administration. KEYWORDS: social security law, social insurance, social assistance, sustainability, Slovenia